CUSTOMER ACCEPTANCE OF DIGITAL BANKING: A STUDY ON GOVERNMENT’S BANK IN GREATER JAKARTA - Marthadinata Hutagaol; Togar Alam Napitupulu (Jurnal Darma Agung, 2022)
The development of information technology at this time has succeeded in providing an evolution that leads to digital-based banking services (digital banking) in Indonesia. This is driven by the need for convenience in making payment transactions in Indonesian society. However, the process of digitizing banking services in Indonesia is still relatively slow. User acceptance of digital banking service applications is one of the supporting factors for the successful application of digital banking technology today. This study aimed to measure the acceptance of digital banking by customers of Government Bank in Greater Jakarta (Jakarta, Bogor, Depok, Tangerang, Bekasi) by using the UTAUT 2 model. This study used a sample of 100 respondents to scrutinize the respondents' views based on variables: performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit, trust, perceived risk, and knowledge. Data Analysis was performed using Structural Equation Modelling Partial Least Square (SEM-PLS). The results of the convergent validity test showed that all indicators have a loading factor value above 0.7, and the reliability test results show the value of Cronbach's Alpha above 0.7, which indicates that the variable is valid for further testing. The structural equation model with behavioral intention and using behavior as a dependent variable indicated that some variables had no significant effect. The results of the p-values test show that performance expectancy, and facilitating conditions have a significant effect on behavioral intentions and that behavioral intentions, trust, and knowledge have a significant effect on use behavior.